Pengaruh latihan killer pass dan pass combination terhadap ketepatan passing (passing accuracy) dalam permainan sepakbola pada atlet usia 10-13 tahun di klub ps. tulen lombok timur tahun 2023 - Zen Ali; Mujriah; Sukarman (Journal Transformation of Mandalika, e-ISSN: 2745-5882, p-ISSN: 2962-2956, 2024)
The aim of this study is to increase passing accuracy by using the Killer Pass (X1) and Pass Combination X2 exercises on athletes aged 10-13 years at Club PS Tulen East Lombok in 2023.The method used in this study was a quasi-experimental "One groups pretest-posttest design" without a control group with the passing accuracy test instrument and using a purposive sampling technique in sampling.The sample used was 22 athletes aged 10-13 years at the East Lombok PS Tulen Club in 2023. Data analysis in this study used statistical data analysis using the t-test formula. Group A as the experimental group was given a killer pass exercise and group B was given a combination of pass exercises. This training program lasts for 5 weeks with 3 exercises in one week.The results of the t-count test for Killer Pass (X1) to Passing Accuracy (Y) are 4.52 and Pass Combination (X2) is 7.98 to Y while the t-table value is 2.22 with a Sig value of 0.05, these results indicate that there is a significant difference so that the alternative hypothesis (Ha) is rejected and the null hypothesis (H0) is accepted.The conclusion based on the results of the study shows that there is a significant effect of the Killer Pass and Pass Combination exercises on the passing accuracy (Passing Accuracy) of SSB Club PS Tulen East Lombok football players in 2023.